Adaptation to the waste anesthesia gas system: Gaps in knowledge and opportunities for positive environmental impact - John Palmisano; Michael Deininger (Journal of Advanced Veterinary and Animal Research, 2015)
Canisters containing activated charcoal are commonly used in the laboratory setting to collect waste anesthetic gas (WAG). This requires the weighing of the WAG canister after each use and for investigators to maintain an accurate time log of anesthesia duration. A typical rodent anesthesia station may include the use of 3 WAG canisters; one for the anesthesia induction box, one for the operative table, and one for gas monitoring. To simplify the anesthesia breathing circuit, we have developed a “T” connector that replaces the need for having multiple WAG canisters. The “T” connector directs the waste anesthetic from multiple sources; the anesthesia induction box, operative table and gas monitor into a single WAG canister. Use of the “T” connector appears to be a safe, acceptable device that conveniently directs waste gas while improving charcoal adsorption within the canister. In addition, this device may have a positive impact on the environment with a secondary benefit of possible cost savings associated with the purchase and disposal of the hazardous waste contents.